How do you simplify the product #(2n - 3)(n^2 - 2n + 5)# and write it in standard form?

1 Answer
May 11, 2017

Answer:

#2n^3-7n^2+16n-15"#

Explanation:

Multiply each term in the second bracket by each term in the first bracket as shown below.

#(color(red)(2n-3))(n^2-2n+5)#

#=color(red)(2n)(n^2-2n+5)color(red)(-3)(n^2-2n+5)#

#=(color(red)(2n)xxn^2)+(color(red)(2n)xx-2n)+(color(red)(2n)xx5)#

#color(white)(=)+(color(red)(-3)xxn^2)+(color(red)(-3)xx-2n)+(color(red)(-3)xx5)#

#=2n^3-4n^2+10n-3n^2+6n-15#

#=2n^3-7n^2+16n-15larr" in standard form"#